Vaginal delivery Postpartum Hemorrhage: Incidence, Risk Factors, and Causes - Nazpari Ashouri; Masoumeh Kordi; Mohammad-Taghi Shakeri; Fatemeh Tara (Mashhad University of Medical Sciences, 2019)
Introduction: Postpartum hemorrhage is considered as one of the major causes of maternal mortality in the world. Identification of women at risk of postpartum hemorrhage prepares the medical team for faster therapeutic decisions which can reduce maternal complications. This study was performed with aim to identify the risk factors of vaginal delivery postpartum hemorrhage. Methods: This cross-sectional analytic study was performed on 600 women referred to Omol-Banin Hospital of Mashhad in 2017. After delivery, the researcher measured and recorded lost blood volume in mothers via plastic blood collection bags and pads within 4 hours after delivery. Data were analyzed by SPSS software (version 25) and Mann-Whitney, independent t, Chi-square, and Fisher Exact tests. P<0.05 was considered statistically significant. Results: PPH occurred in 33.3% of deliveries in this study. The results of the logistic regression test showed significant relationship between PPH and nulliparity (OR:5.987،CI:1.870-8.821)، hemoglobin level (OR:1.849،CI:1.677-2.890)، platelet levels (OR:2.955،CI:1.989-3.001)، Afghan race (OR:3.645،CI:1.141-8.644)، Barbarian race (OR:5.958،CI:3.452-6.645)، history of PPH(OR:4.562، CI:1.570-6.597)، preeclampsia(OR:20.126،CI:3.831-21.114)، duration of the second stage (OR:4.452،CI:2.265-5.674)and third stage(OR:3.620،CI:1.857-6.325) of labor، consumption of Magnesium sulfate(OR:67.107،CI:60.471-69.101)، uterine fundal pressure(OR:4.941،CI:3.305-5.903)، use of vacuum(OR:14.123،CI:10.003-18.831)، episiotomy(OR:2.143،CI:2.136-3.349)، genital tract tears(OR:17.889،CI:14.152-18.950), neonatal birth weight(OR:4.025،CI:3.641-6.850)، placenta weight(OR:3.988،CI:2.980-3.997)، and courage (OR:15.005،CI:13.520-15.224) were each associated with an increased odds of PPH. Conclusion: The most important cause of postpartum hemorrhage is uterine atony and the most important risk factors are nulliparity، Afghan and Barbarian race، history of PPH، preeclampsia، increased duration of the second and third stage of labor، consumption of Magnesium sulfate، uterine fundal pressure، use of vacuum، genital tract tears، placenta weight، neonatal birth weight and courage.